Characterization of ferrochrome ash and blast furnace slag based alkali-activated paste and mortar - Omur, Tarik; Miyan, Nausad; Kabay, Nihat; Birol, Burak; Oktay, Didem (ELSEVIER SCI LTD, 2023)
Ferrochrome ash (FCA) is an industrial waste material which when disposed causes environmental pollution and health hazard. Therefore, in this paper, FCA replaced up to 30 % of blast furnace slag (BFS) to investigate its possible utilization by producing alkali-activated material. The effect of FCA content and varying Na2O dosage on fresh, physicomechanical and microstructural properties was discussed. The addition of FCA improved the rheological properties of mixes by reducing plastic viscosity from 47.3 to 22.9 Pa.s and from 129.2 to 71.1 Pa.s and yield stress from 87.5 to 40.7 Pa and from 89.8 to 44.0 Pa for Na2O dosage of 6 and 10 %, respectively. This allowed reduction of water content, which in turn resulted in similar or superior physicomechanical properties compared to the control mixtures. The setting time was prolonged with an increase in Na2O dosage and FCA addition and was mainly governed by the initial molar ratio of SiO2/Al2O3. The increase in FCA ratios consis-tently decreased semi-adiabatic peak temperature and time to reach the peak temperature. FCA addition decreased compressive strength and drying shrinkage of mortar mixes, whereas increase in Na2O dosage significantly enhanced strength. The microstructural investigations revealed that the major reaction products of paste mixes were C-S-H, C-A-S-H, and/or M-S-H gels, along with minor phases such as forsterite, natrolite, brownmillerite, and spinel. The formation of M-S-H type gels was observed with an increased replacement ratio of FCA. In addition, the polymerization of main reaction products is found to be controlled by the Ca/Si and Si/Al ratios as revealed by microstructural analysis. The findings of this research point out the viability of producing BFS and FCA-based alkali-activated material with reasonable properties and their efficient utilization which may ensure sustainability.
Keywords: Alkali -activation; Ferrochrome ash; Microstructure; Rheology; Physicomechanical properties; WATER-TREATMENT-SLUDGE; RICE HUSK ASH; STRENGTH PROPERTIES; DRYING SHRINKAGE; PORTLAND-CEMENT; GEOPOLYMER; CONCRETE; PERFORMANCE; Construction & Building Technology; Engineering; Materials Science